Teachers’ Knowledge about Higher-order Thinking Skill and It’s Implementation in Teaching Reading Classroom: A Case Study in a Higher Secondary School in Indonesia - Desy Pusparini; Suparno Suparno; Teguh Sarosa (Universitas Islam Nahdlatul Ulama Jepara, 2020)
ABSTRACTHigher-order Thinking Skills (HOTS) is a well-known term that is nowadays being discussed among researchers, especially in education contexts. In this globalization era, developing students’ ability to think with HOTS becomes teachers’ challenging task to do. They are responsible to enrich their knowledge about HOTS and update findings and ideas of HOTS implementation in teaching. So, they will be able to implement HOTS in teaching they believe will be ideal and effective to develop students’ HOTS. This research aims to investigate teachers’ knowledge about HOTS and investigate how they implement their knowledge of HOTS in teaching reading classroom. This is a qualitative research with case study as the research design. The data were collected using in-depth interviews followed by observation. The participants of this research are three English teachers from a senior high school who teach different grades. The results of this research show that the teachers’ knowledge of HOTS is still low. They do not understand HOTS conceptually. However, their implementation of HOTS in teaching reading show that they implement HOTS to teach reading that enables students to activate their HOTS. They include the concept of effective HOTS teaching suggested by Fogarty (2009).